2020
DOI: 10.1097/rlu.0000000000003059
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT in Sporadic Creutzfeldt-Jakob Disease

Abstract: We report the case of a 64-year-old man referred for optic ataxia, constructional apraxia, and spatial orientation disorders evolving for 2 months. Benson syndrome (posterior cortical atrophy) was initially suspected. Brain 18F-FDG PET/CT depicted an asymmetric decreased uptake pattern consistent with Creutzfeldt-Jakob disease. 14-3-3 proteins were detected in the cerebrospinal fluid. Clinical evolution was quickly unfavorable. The patient died 1 month after the PET/CT, and Creutzfeldt-Jakob disease was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…En cuanto a la 18 F-FDG-PET/TC, se han señalado hallazgos característicos que se pueden encontrar incluso antes de observarse anomalías en la RM (2) y consisten en áreas hipometabólicas en las zonas afectadas, generalmente bilaterales y asimétricas. La región temporal medial, el cerebelo y los ganglios basales con frecuencia se encuentran menos comprometidos (1,7).…”
Section: Discussionunclassified
“…En cuanto a la 18 F-FDG-PET/TC, se han señalado hallazgos característicos que se pueden encontrar incluso antes de observarse anomalías en la RM (2) y consisten en áreas hipometabólicas en las zonas afectadas, generalmente bilaterales y asimétricas. La región temporal medial, el cerebelo y los ganglios basales con frecuencia se encuentran menos comprometidos (1,7).…”
Section: Discussionunclassified
“…Although initial DWI (A) showed no significant lesions on cortex or basal ganglia, dual FP-CIT PET shows showed hypometabolism in the bilateral occipitoparietal, basal ganglia, and thalamus on early phase (B) with diffuse decreased DAT uptake in delayed phase (C) (more affected on right), which is different of typical corticobasal syndrome. 4,5 Follow-up brain MRI (2 weeks later) showed high signal intensity lesions in cortex and basal ganglia on DWI (D) corresponding to hypoperfusion area of initial early phase FP-CIT PET. CSF studies 14-3-3 protein assay showed positive result.…”
Section: Figurementioning
confidence: 99%
“…In contrast to extensive structural neuroimaging data, limited information is available about the characteristics and diagnostic utility of metabolic brain imaging. Case reports [10–13] and small case series [14–16] showed pronounced hypometabolism in various cortical and subcortical areas in CJD patients. The hypometabolic brain areas were concordant with MRI changes but more pronounced [16, 17].…”
Section: Introductionmentioning
confidence: 99%